TO FIND OUT THE ETIOLOGY OF LOWER GASTROINTESTINAL TRACT BLEEDING IN PEDIATRIC PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
Background: Lower gastrointestinal tract bleeding (LGIB) is a clinical condition in children that belongs to a wide range of etiologies. Good patient outcomes are achieved through early diagnosis and proper management. This study was done to examine the potential causes of LGIB in children presenting to a tertiary care hospital.Objective: This study aims to identify and analyze the causes of lower gastrointestinal tract bleeding among children.Methods: This was a cross-sectional observational study that was conducted from 1st October 2024 to 31st March, 2025 at the Pediatric Gastroenterology Unit, a tertiary care hospital, in Rawalpindi. LGIB-affected symptomatic pediatric patients were utilized, and history, physical examination, blood tests, endoscopy, colonoscopy, and imaging were deemed the approach to diagnosis.Results: The discussed paper identified inflammatory bowel disease (35%) and infectious gastroenteritis (30%) as the most common causes of LGIB. Other major causes were vascular malformations and Meckel's diverticulum.Conclusion: Etiology-specific therapy and early diagnosis can have a significant impact on pediatric LGIB outcomes. To manage effectively, a multidisciplinary approach is needed.